Congenital malaria in China. - Zhi-Yong Tao; Qiang Fang; Xue Liu; Richard Culleton; Li Tao; Hui Xia; Qi Gao (Public Library of Science (PLoS), 2014)
BACKGROUND: Congenital malaria, in which infants are directly infected with malaria parasites from their mother prior to or during birth, is a potentially life-threatening condition that occurs at relatively low rates in malaria-endemic regions. It is recognized as a serious problem in Plasmodium falciparum-endemic sub-Saharan Africa, where recent data suggests that it is more common than previously believed. In such regions where malaria transmission is high, neonates may be protected from disease caused by congenital malaria through the transfer of maternal antibodies against the parasite. However, in low P. vivax-endemic regions, immunity to vivax malaria is low; thus, there is the likelihood that congenital vivax malaria poses a more significant threat to newborn health. Malaria had previously been a major parasitic disease in China, and congenital malaria case reports in Chinese offer valuable information for understanding the risks posed by congenital malaria to neonatal health. As most of the literature documenting congenital malaria cases in China are written in Chinese and therefore are not easily accessible to the global malaria research community, we have undertaken an extensive review of the Chinese literature on this subject. METHODS/PRINCIPAL FINDINGS: Here, we reviewed congenital malaria cases from three major searchable Chinese journal databases, concentrating on data from 1915 through 2011. Following extensive screening, a total of 104 cases of congenital malaria were identified. These cases were distributed mainly in the eastern, central, and southern regions of China, as well as in the low-lying region of southwest China. The dominant species was P. vivax (92.50%), reflecting the malaria parasite species distribution in China. The leading clinical presentation was fever, and other clinical presentations were anaemia, jaundice, paleness, diarrhoea, vomiting, and general weakness. With the exception of two cases, all patients were cured with antimalarial drugs such as chloroquine, quinine, artemether, and artesunate. CONCLUSIONS: The symptoms of congenital malaria vary significantly between cases, so clear and early diagnosis is difficult. We suggest that active surveillance might be necessary for neonates born to mothers with a history of malaria.